2022
DOI: 10.3390/molecules27185838
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Analysis of Microflora and Metabolites in the Development of Ulcerative Colitis into Colorectal Cancer Based on the Lung–Gut Correlation Theory

Abstract: The lungs and large intestine can co-regulate inflammation and immunity through the lung–gut axis, in which the transportation of the gut microbiota and metabolites is the most important communication channel. In our previous study, not only did the composition of the gut microbiota and metabolites related to inflammation change significantly during the transition from ulcerative colitis (UC) to colorectal cancer (CRC), but the lung tissues also showed corresponding inflammatory changes, which indicated that g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The alteration of the linoleic acid metabolism pathway has been associated with different tumor types. Altered content of membrane PCs and phospholipid (PL) profiles have also been associated with cancer development and progression. Lower plasma LPC levels have been suggested as markers of severity in cancer, including RCC with lower levels exhibited in more aggressive tumors, and increased levels in patients who were in remission 6 months after surgery . However, different trends were reported for PC 16:0 in RCC. , More studies are needed to understand how the PL metabolism is altered and regulated and to decipher the particular role of specific PLs in a pathological context.…”
Section: Resultsmentioning
confidence: 99%
“…The alteration of the linoleic acid metabolism pathway has been associated with different tumor types. Altered content of membrane PCs and phospholipid (PL) profiles have also been associated with cancer development and progression. Lower plasma LPC levels have been suggested as markers of severity in cancer, including RCC with lower levels exhibited in more aggressive tumors, and increased levels in patients who were in remission 6 months after surgery . However, different trends were reported for PC 16:0 in RCC. , More studies are needed to understand how the PL metabolism is altered and regulated and to decipher the particular role of specific PLs in a pathological context.…”
Section: Resultsmentioning
confidence: 99%
“…A growing body of research suggests that the microbiome is crucial in inflammatory pulmonary disorders such as acute lung injury (ALI) and acute respiratory distress syndrome. Tang et al discovered that the transition from ulcerative colitis (UC) to colorectal cancer (CRC) significantly altered not only the composition of the gut microbiota and metabolites associated with inflammation but also the lung tissues, which demonstrated that gastrointestinal illnesses can result in pulmonary illnesses (Tang et al, 2022). Yoon et al found that the composition of the gut microbiota has a significant impact on BLM-induced wasting and death, suggesting a role for the lung-gut axis in lung injury.…”
Section: Figurementioning
confidence: 99%
“…Tang et al. discovered that the transition from ulcerative colitis (UC) to colorectal cancer (CRC) significantly altered not only the composition of the gut microbiota and metabolites associated with inflammation but also the lung tissues, which demonstrated that gastrointestinal illnesses can result in pulmonary illnesses ( Tang et al., 2022 ). Yoon et al.…”
Section: Close Relationship: Gm and Nsclcmentioning
confidence: 99%
“…ω-6 fatty acids include arachidonic acid (AA) and linoleic acid, which are often associated with promoting UC pathogenesis ( 14 ). Accumulating evidence from population-based revealed an increased level of AA in the colonic mucosa of UC patients ( 154 ) associated with IBD-related colorectal cancer progression ( 156 , 157 ). Metabolomic analysis indicated perturbed AA metabolism in UC mucosa ( 158 ), and an increased likelihood of ω-6 fatty acid depletion in pediatric IBD patients ( 159 ).…”
Section: Long-chain Fatty Acidsmentioning
confidence: 99%